Health promoting ideas and actions generated by community engagement in an underserved Swedish area. (13th November 2019) - Magnusson, M; Forslund, H B; Berg, C; Wretlind, K; Hallmyr, M; Hedström, C; Vaughn, L M
Abstract: Background: For an intervention to contribute to decreased health gaps, people living in underserved areas must participate in the research-to-action process during the development of the intervention. Methods for increased engagement and participation have been developed within the community-based participatory research (CBPR) paradigm. Group Level Assessment (GLA) is a qualitative, participatory methodology that is designed for a large group to generate and evaluate relevant needs and priorities within a lens of action for positive social change. Influence of researchers is tuned down in favour of partnership and impact from the community. Ideally, the process results in participant-driven data and relevant action plans. The aim was to apply GLA to generate reflections on the situation in the community, aligning towards action for change. Methods: We applied GLA together with people living in Gårdsten, an underserved Swedish suburb where obesity, caries and other illnesses are prevalent. Residents were recruited by posters and post cards at a community center and by snowball sampling. In total, 47 residents attended at least one of eight GLA sessions held over a five-month time period. The majority were women. Outcomes were reflections, suggestions and actions for change. Results: Themes were: resident pride of the area, the importance of communication and of places to meet, a feeling of being abandoned by society, and a desire for more collaboration between schools and parents. Immediate results were a language café and inquiries from the community about information regarding teeth, food and health. When the results were presented for stakeholders in a report and an exhibition, new collaborations were founded and old were refreshed. Conclusions: GLA helped residents identify what they thought valuable and relevant concerning health issues and supported them in taking actions to achieve change. Key messages: Participatory processes that directly engage community residents can result in fruitful discussions and actions. Methodologies like GLA that support such processes may contribute to closing the health gap.